The 1980s as (an Attempt in) the Decolonialization of Malaysian Art - Abdullah, Sarena (NUS Press, 2020)
In Malaysia, the implementation of the National Culture Policy in the early 1970s reiterated the ethnic preference policy of the National Economic Policy (NEP). As a result, the subsequent 1971 National Culture Congress (NCC) and the Islamization Policy undertaken by the government in the late 1970s had great influence on art practices in Malaysia, especially during the 1980s. These policies could be seen as an official attempt to shape the Malaysian identity, especially in terms of visual art in post-Independence Malaysia. The first part of this article will discuss the indirect consequences of the 1971 National Culture Policy and several Islam-centred policies since the late 1970s and how several assertions were made through a few writings about Malaysian art: that only certain modern art forms, aligned with the rhetoric of national agendas, were produced and exhibited in the late 1970s until the mid-1990s. This paper will problematize the assertion by discussing some disjuncture and inconsistencies in relation to this narrative of Malaysian art.